Cytotoxicity of Clinacanthus nutans and mechanism of action of its active fraction towards human cervical cancer cell line, HeLA - Siti Nur Fatihah Mohd Roslan,; Yusmazura Zakaria,; Hasmah Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Traditionally, Clinacanthus nutans (CN) or locally named as ‘Belalai Gajah’ is one of the herbal plant claimed to be able to treat cancer. The aimd of this study are to extract, isolate and characterize the active anticancer compound from CN and to determine the mode of cell death induced by the compound. Bioassay guided fractionation was done on the CN extract by using column chromatography. The cytotoxicity activities of these fractions toward HeLA cells were examined by MTT assay. The nuclear morphology was examined by Hoechst 33258 staining and the cell cycle arrest was evaluated by propium iodide staining using flow cytometry. The presence of active compound in the chosen fraction was determined by Liquid Chromatography Mass Spectrometry (LCMS). Out of 16 fractions collected, Fraction 11(F11) showed the lowest IC50 value with 27 ± 2.6 μg/mL. The value of IC50 for F11 towards normal cell, NIH 3T3 cell and L929 cell, were 70 ± 4.0 μg/mL and 45 ± 1.5 μg/mL respectively. These values were higher than tamoxifen, therefore indicating that tamoxifen is more toxic towards normal cells compared to F11. Nuclear morphology of HeLA cell displayed DNA fragmentation, nuclear condensation and formation of apoptotic bodies upon treatment with F11 for 24 hours. The cell cycle distribution of HeLA cell treated with F11 was arrested at G1 phase. The active compound identified to potentially possess the anticancer property is 19-Oxo-all-trans-retinoic acid. In conclusion, 19-Oxo-all-trans-retinoic acids from F11 of the CN extract, is a potential anticancer agent for cervical cancer.